Frontal sinus obliteration with heterogeneous corticocancellous bone versus spontaneous osteoneogenesis in monkeys (Cebus apella): Histologic analysis - Vieira, Eduardo Hochuli [UNESP]; Gabrielli, M. F. R.; Garcia, I. R.; Gabrielli, M. A. C. (W B Saunders Co, 2003)
Purpose: In this study, we evaluated the results of spontaneous osteoneogenesis of the frontal sinus with autogenous bone plug versus obliteration with heterogeneous (human) bone in monkeys (Cebus apella).Materials and Methods: Eight young adult male C apella monkeys underwent an ostectomy of the anterior wall of the frontal sinus, removal of the sinus mucosa, and inner decortication of the bony walls and then were divided into 2 groups of 4 each, as follows. Group I monkeys underwent obliteration of the nasofrontal ducts with a free segment of frontallis muscle and corticocancellous heterogeneous bone, followed by full obliteration of the sinus with corticocancellous heterogeneous bone (Dayton Regional Tissue Bank, Dayton, OH). Group II monkeys underwent obliteration of the nasofrontal ducts with a frontal muscle segment and tibial autogenous bone plug, without full obliteration of the frontal sinus. In all animals, the sinus anterior wall was repositioned and fixed with 1.0 plate and screws. The monkeys were killed after 180 days, and routine laboratory procedures were followed for hematoxylin-eosin staining and histologic evaluation of the specimens.Results: the 2 studied techniques were both effective in obliterating the frontal sinus with newly formed bone. The nasofrontal ducts were obliterated by new bone formation or fibrous tissue (1 animal only).Conclusions: Both methods used for frontal sinus obliteration were effective; the heterogeneous bone (human bone) was well tolerated and presented low antigenicity. The nasofrontal duct obliteration with autogenous muscle associated with autogenous tibial bone (group II) or with heterogeneous bone (group I) was effective, isolating the frontal sinus from the nasal cavity. The spontaneous obliteration resulted, in the period analyzed, in earlier bone maturation compared with the obliteration by heterogeneous bone. (C) 2003 American Association of Oral and Maxillofacial Surgeons.